Sosialisasi Model Pembelajaran Sentra Sebagai Implementasi Merdeka Belajar Anak Usia Dini - Ajeng Rizki Safira; Rr. Agustien Lilawati (LPMP Imperium, 2022)
The socialization with the theme of the central learning model as the implementation of independent learning for early childhood has the aim of conveying the basic principles of the central learning model that can be used as a form of independent learning for the level of students. This is based on implementing the central learning model, which is not following the principles but is currently being demanded by the existence of an independent learning era. Participants have explained the central learning model, its principles, and its implementation. In addition, it also explains the meaning of independent learning and its relationship to the central learning model. This activity was carried out at the NU 42 Nurul Ulum Kindergarten in Gresik. The participants who took part in this activity were ten teachers and school principals. There were many positive responses which could be seen from the enthusiasm of the questions asked and the interesting question and answer process.